Radiation-induced chromosome aberrations in oncogynecological patients and patients with head and neck cancer undergoing radiotherapy on a linear accelerator - Maznyk, Nataliya; Sypko, Tetiana; Sypko, Tetiana; Pshenichna, Nataliya; Pshenichna, Nataliya; Starenkiy, Viktor; Starenkiy, Viktor; Krugova, Iryna; Krugova, Iryna (ScienceRise: Biological Science, 2018)
Aims: The assessment of radiation-induced chromosome aberrations in lymphocytes of oncogynecological and head and neck cancer patients during radiation therapy on linear accelerator depending on the tumor localization. Methods: 16 oncogynecological patients and 12 patients with head and neck tumors undergoing radiation treatment on linear accelerator were examined. Lymphocytes were cultivated by the conventional technique before treatment, in the middle and at the end of the radiotherapy course. Radiation doses exceeded 40–44 Gy. Results of research: The yield and range of radiation-induced cytogenetic damage changes in lymphocytes during megavolt radiation therapy were demonstrated. The monotonic increase of chromosome type aberrations from start to the end of treatment was found. More pronounced changes in these parameters in oncogynecological patients than in patients with head and neck tumors were demonstrated. The range of cells with chromosome aberrations expanded during radiotherapy in both groups. In the middle of the radiotherapy cells with 1–4 aberrations per cell in head and neck cancer patients and 1–7 aberrations per cell in oncogynecological patients were observed. At the end of radiotherapy the number of damages per aberrant cell from 1 to 8 for both groups was observed. The distribution of the chromosome type aberrations among cells was found to be over-dispersed according to Poisson statistic both at the middle and at the end of radiotherapy course. Conclusion: The study of the radiation-induced aberrations revealed the different character of cytogenetic damages accumulation in patients undergoing radiotherapy depending on tumor localizations and accordingly on the irradiated body fraction. The data obtained will expand the knowledge concerning effects of fractionated therapeutic megavolt radiation in non-tumor tissues of patients